Automatización de un taladro de árbol para madera - Carrera-Carrera, Joseph Anthony; Méndez-Pallares, Baldomero (Visión electrónica, 2018)
The present document shows alternative of design to automate a drill wood tree, given the function characteristics: positioning, the feeding system, the deepness of drilling and the marking of each of these worked pieces. With the automation of the drill and it different stations, this intention is to increase the productive, warranting a better quality and offering to the operator less physic effort, already it only required supply the raw material to the feeding system, also to monitoring and supervise this process. It shown us the sketches and designs proposed, also the components and mechanism selected to achieve integrate the manufacturing process that implying to automation this process.